The Existence of Murals in Supporting the Aesthetics of Tourism Villages - Amir Sarifudin; Muhammad Jazuli; Muh Ibnan Syarif (International Conference on Science, Education, and Technology, 2022)
Abstract. This article discusses the existence of a mural in supporting the aesthetics of a tourist village in Babakan Village, Tangerang, Banten. The village was originally a slum village after participating in the thematic village program organized by the Tangerang City government which then transformed into a clean, tidy village and has a tourist attraction. The purpose of this research is to find out how big the role of murals is in supporting the aesthetics of Kampung Babakan. This study uses descriptive qualitative methods, using data collection techniques through observation, interviews and literature study. The data is then reduced, displayed and then conclusions are drawn. The method used is a case study, in this approach the researcher explores or explores a phenomenon in society that arises because of an event, namely the creation of a tourist village. The results of this study show that the mural in Kampung Babakan is one of the attractions for tourists who come to visit it.